Tingkat Aktivitas Fisik Mahasiswa STAI Al-Gazali Soppeng Angkatan 2021 - Muhajirin L; Akbar Sudirman (Departement of Mathematics Education, 2024)
This research aims to determine the level of physical activity among students of the Islamic Religious Education Program at Al-Gazali School of Islamic Religion (STAI) Soppeng, class of 2021, as measured through the IPAQ questionnaire system. This research uses a quantitative method with a descriptive survey research design. The subjects of this study are 30 students from the Islamic Religious Education Program at Al-Gazali School of Islamic Religion (STAI) Soppeng, class of 2021. The data analysis used is univariate analysis. The results of this research show that the level of physical activity among students of the Islamic Religious Education Program at Al-Gazali School of Islamic Religion (STAI) Soppeng, class of 2021, falls into the